Anemia Prevalence and Risk Factors in Two of Ethiopia’s Most Anemic Regions among Women: A Cross-Sectional Study - Gebru Gebremeskel Gebrerufael; Bsrat Tesfay Hagos (Advances in Hematology, 2023)
Background. In Sub-Saharan African (SSA) nations, including Ethiopia, anemia is a significant public health issue. Ethiopia has continued to bear the enormous burden of anemia infections. Over time, the prevalence of anemia has significantly increased in Ethiopia. In addition, there is a paucity of literature and regional variations in the pace of increment expansion. Therefore, the primary goal of this study was to evaluate the prevalence of anemia and risk factors among women in Ethiopia’s two most anemic regions. Methods. 2,519 women participated in a community-based cross-sectional study from January 18 to June 27, 2016. In order to determine the causes of anemia in women in two of Ethiopia’s most anemic regions, an ordinal logistic regression model was taken into consideration. The applicability of the proportional odds test was evaluated using the chi-square test of the parallelism assumption. A p value of 0.05 or below was used to define crucial and statistically significant predictor variables. Results. The overall prevalence rate of anemia was 56.8% (95% CI (54.8%–58.7%)). The chi-square test of the parallelism assumption indicated that the odds ratios were constant across all cut-off points of women’s anemia levels at a 5% significance level (p value = 0.122). Of the severity of anemia levels among women, 48.2, 46.1, and 5.7% had mild, moderate, and severe anemia levels, respectively. In multivariable ordinal logistic regression analyses, being born (lived) in the Somali region (AOR = 1.6, 95% CI: 1.37, 1.90), having a parity of 4–5 (AOR = 1.3, 95% CI: 1.05, 1.66), and having ≥6 children (AOR = 1.4, 95% CI: 1.1, 1.7), being a contraceptive user (AOR = 3, 95% CI: 2.5, 3.6), being currently pregnant (AOR = 2.8, 95% CI: 2.3, 3.4), having no ANC follow-up (AOR = 1.9, 95% CI: 1.6, 2.3), being married women (AOR = 1.4, 95% CI: 1.1, 1.9), and user of unimproved toilet facility (AOR = 1.3, 95% CI: 1.1, 1.6) were significantly positively associated with anemia. Conclusions. Finally, the anemia burden was dangerously greater than the national average. The region, usage of contraceptives, being pregnant at the time, ANC follow-up, toilet facilities, parity, and marital status all had a substantial impact on anemia. Therefore, to lessen the prevalence of anemia in certain parts of Ethiopia, public health initiatives that improve maternal health service utilization are required, such as ANC follow-up to minimize parity.